2015
DOI: 10.3732/ajb.1400296
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of cytotype distribution inAndropogon gerardii(Poaceae)

Abstract: Results indicate that (1) geographic distribution of 6x and 9x individuals is nonrandom; (2) environmental variables are associated with cytotype distribution in A. gerardii; and (3) nearly half of populations surveyed include both 6x and 9x individuals. The persistence of mixed-ploidy populations may reflect a combination of recurrent polyploid formation and the prevalence of clonal reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 107 publications
2
41
0
Order By: Relevance
“…Although geographical segregation of cytotypes has long been recognized, the underlying mechanisms creating these patterns remain poorly understood (McIntyre, 2012). Ecological sorting along environmental gradients and adaptive differences among ploidy levels may trigger habitat divergence (Duchoslav et al, 2010), a possibility which can be examined quantitatively by means of common garden and/or transplant experiments (McIntyre, 2012; Godsoe et al, 2013; Theodoridis et al, 2013; Glennon et al, 2014; McAllister et al, 2015). In our field investigations, we found that diploids occupied habitats at higher altitudes than hexaploids, supporting the previously reported pattern of distribution of different C. angustifolium cytotypes (Husband and Schemske, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although geographical segregation of cytotypes has long been recognized, the underlying mechanisms creating these patterns remain poorly understood (McIntyre, 2012). Ecological sorting along environmental gradients and adaptive differences among ploidy levels may trigger habitat divergence (Duchoslav et al, 2010), a possibility which can be examined quantitatively by means of common garden and/or transplant experiments (McIntyre, 2012; Godsoe et al, 2013; Theodoridis et al, 2013; Glennon et al, 2014; McAllister et al, 2015). In our field investigations, we found that diploids occupied habitats at higher altitudes than hexaploids, supporting the previously reported pattern of distribution of different C. angustifolium cytotypes (Husband and Schemske, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive evolutionary scenario suggests that shifts in ploidy level could result in differential stress tolerances (Levin, 2002; Baack, 2004; Kubátová et al, 2008; Sonnleitner et al, 2010; McAllister et al, 2015), which may underlie the ecological divergence and adaptation of cytotypes to novel environments (Ramsey, 2011). In contrast, the environmentally independent explanations (‘non-adaptive scenarios’) posit that exclusion of minority cytotypes (Levin, 1975) and historical processes (Sonnleitner et al, 2010; McAllister et al, 2015) may be the driving force behind the observed distribution patterns. Diploid C. angustifolium inhabits higher altitudes than polyploids, and a similar pattern has also been observed in Senecio carniolicus (Sonnleitner et al, 2010; Huelber et al, 2015) and Centaurea jacea (Hardy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence for climatic or ecological niche differentiation between different cytotypes of a species is still inconclusive. While some studies have found correlations between cytotype distribution and climate variables and differences in habitat conditions between cytotypes (e.g., Raabová et al., ; Kolář et al., ; Sonnleitner et al., ; Ramsey, ; Richardson and Hanks, ; Mráz et al., ; McAllister et al., ; Visger et al., ; Muñoz‐Pajares et al., ), others have found evidence for shared broad‐scale climatic niches between cytotypes and no evidence for differences in climatic requirements (Godsoe et al., ; Glennon et al., and references therein). Ideally, the study of niche differentiation would include experiments testing the effects of environmental factors on different cytotypes, but there are not many studies involving such experiments (Ramsey, ; Kolář et al., ; McIntyre and Strauss, ).…”
mentioning
confidence: 99%
“…) and that it remains an active evolutionary and ecological process in many lineages (Ramsey ; Soltis & Soltis ; Ramsey & Ramsey ; McAllister et al . ; Wendel ).…”
mentioning
confidence: 99%